Edukasi pasien chronic kidney disease berbasis aplikasi android : buku saku pasien - Ambar Relawati; Ani Syafriati; Habid Al Hasbi; Pipit Nur Fitria (Universitas 'Aisyiyah Yogyakarta, 2018)
This educational innovation follows the development of the times, where mobile phones become the main electronic tool in the wider community. Researchers develop these innovations by providing general education about chronic kidney failure, nutritional diet and fluid restrictions packed inside an android app. It aims to allow patients to easily access information about chronic renal failure in an increasingly sophisticated technological era. In addition to the information, researchers also added some additional menus or features of the profile, calculator GFR, daily reminder, UF recordings that help patients to facilitate the recording on the phone. Educational counseling android-based applications for two days ie 15-16 January 2018 in the Hemodialisa unit PKU Muhammadiyah Gamping Hospital. Respondents were given education as many as 30 people. The results of the pre and post test questionnaires were processed using SPSS version 16 with Wilcoxon's pre-post test nonparametics. Based on the results obtained for pre and post test of p value 0,000. Applications android Pocket Book Patient This dialysis provides benefits and improves the knowledge of patients who run dialysis in a modern way and easy to access both patients and families.